The political economy of punishment today: visions, debates and challenges - Melossi, Dario; Sozzo, Máximo; Brandariz García, José Ángel (Routledge critical studies in crime, diversity and criminal justice, 2018)
An introduction / José A. Brandariz-García, Dario Melossi and Máximo Sozzo -- Between struggles and discipline : Marx and Foucault on penality and the critique of political economy / Dario Melossi -- The renaissance of the political economy of punishment from a comparative perspective / Máximo Sozzo, 3. For and Against the Political Economy of Punishment : Thoughts on Bourdieu and Punishment / Ignacio González-Sánchez -- Do economic depressions reduce the use of fines? : revisiting Rusche and Kirchheimer's punishment and social structure / Patricia Faraldo Cabana -- From one recession to another : the lessons of a long-term political economy of punishment : the example of Belgium (1830-2014) / Charlotte Vanneste -- Political economy and punishment in Australia / Hilde Tubex -- Punishment in a hybrid political economy : the Italian case (1970-2010) / Zelia A. Gallo -- "A return to gulags"? explaining trends in post-Soviet prison rates / Gavin Slade -- Inclusion's dark side : the political economy of irregular migration in Greece / Leonidas K. Cheliotis -- Reflections on Spanish policies of migration control : a political economic reading on the punishment of migrants / José Ángel Brandariz-García